Letter to Jane Tolmach from Julius Gius - Julius Gius:::::: (1961)
A letter to Jane Tolmach from Julius Gius, Editor at the Ventura County Star Free Press. The letter shares that he tried to encourage Senator Jackson to visit the county but unfortunately he was not able to visit.